Quality improvement of pediatric colonoscopy by application of bundle and centralization: A single-center review - Shu-Chao Weng; Hung-Chang Lee; Chun-Yan Yeung; Wai-Tao Chan; Hsuan-Chih Lao; Chuen-Bin Jiang (Pediatrics and Neonatology)
Background: To assess the quality change of our single-center pediatric colonoscopy after applying bundle for bowel preparation and general anesthesia and centralize the procedure using terminal ileum (TI) intubation rate as the main indicator. Methods: All elective colonoscopies performed for patients younger than 18 years old in MacKay Memorial Hospital from July 2015 through June 2020 (assigned to group 1, before bundle) and from August 2020 through July 2021 (assigned to group 2, after bundle) were retrospectively reviewed for demographic characteristics, indications, bowel preparation agent and cleansing level, diagnostic and therapeutic procedures, maximum intestinal level reached, and cecal intubation and total procedure time. Statistical analysis was done using P value < 0.05 considered to be significant. Results: Analysis included 45 and 32 colonoscopies in group 1 and 2, respectively. Bloody stool was the most frequent indication in both groups. Both TI intubation rate (42.2 % vs. 75.0 %, P = 0.004) and biopsy rate (45.0 % vs. 75.9 %, P = 0.01) increased significantly from group 1 to group 2. The narrower standard deviation of bowel preparation score (1.93 vs. 1.15) and total procedure time (37.71 vs. 22.29) in group 2 indicated a more stable quality, although the mean showed no difference. There was no statistical difference in age, gender, body weight, cecal intubation rate, or cecal intubation time. Conclusion: A higher TI intubation rate and biopsy rate indicated an improved quality of pediatric colonoscopy after applying bundle including bowel preparation and general anesthesia, with additional centralization.